Soft X-ray signatures of cationic manganese–oxo systems, including a high-spin manganese(v) complex. Issue 6 (1st February 2022) - Delcey, Mickaël G.; Lindblad, Rebecka; Timm, Martin; Bülow, Christine; Zamudio-Bayer, Vicente; von Issendorff, Bernd; Lau, J. Tobias; Lundberg, Marcus
Abstract : Limitations in synthesis of high-valent metal–oxo complexes are circumvented by trapping a series of ionic Mn–oxo complexes. One of them is a rare high-spin Mn(v )–oxo, which can serve as a template to identify similar intermediates in catalysis. Abstract : Manganese–oxo species catalyze key reactions, including C–H bond activation or dioxygen formation in natural photosynthesis. To better understand relevant reaction intermediates, we characterize electronic states and geometric structures of [MnO n ] + manganese–oxo complexes that represent a wide range of manganese oxidation states. To this end, we apply soft X-ray spectroscopy in a cryogenic ion trap, combined with multiconfigurational wavefunction calculations. We identify [MnO2 ] + as a rare high-spin manganese(v ) oxo complex with key similarities to six-coordinated manganese(v ) oxo systems that are proposed as reaction intermediates in catalytic dioxygen bond formation.